1978
DOI: 10.1016/s0022-5347(17)57325-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ureteral Colic with Intravenous Indomethacin

Abstract: A randomized prospective double-blind study of the analgesic effect of 50 mg. intravenous indomethacin, a prostaglandin synthesis inhibitor, was done on 47 consecutive patients with acute ureteral colic. The placebo used was 5 mg. intravenous riboflavin because of the same color as indomethacin. Indomethacin provided complete relief in 78 per cent of the cases, while riboflavin provided relief in 30 per cent. The difference is statistically significant. No side effects were observed with indomethacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…The drug may interrupt the trans port of urine from the kidney to the bladder, and may thus have an adverse effect on the urologic tract. On the other hand, this inhibitory effect may be useful for treat ment of pain induced by renal colic, since it is reported that non-steroid anti-inflammatory drugs reduce the con tractility of ureteral and renal pelvic smooth muscle and the effects contribute to the pain relief in the patient (6,9,23,24).…”
Section: Effects Of Drugs On Ureteral Peristaltic Functionmentioning
confidence: 99%
“…The drug may interrupt the trans port of urine from the kidney to the bladder, and may thus have an adverse effect on the urologic tract. On the other hand, this inhibitory effect may be useful for treat ment of pain induced by renal colic, since it is reported that non-steroid anti-inflammatory drugs reduce the con tractility of ureteral and renal pelvic smooth muscle and the effects contribute to the pain relief in the patient (6,9,23,24).…”
Section: Effects Of Drugs On Ureteral Peristaltic Functionmentioning
confidence: 99%
“…In postulated in the upper urinary tract but the picture emergthe urinary bladder, prostanoids are produced during bladder ing from the available data is far from clear (see below). The distension at cystometry and exert both a direct myotropic tissue is of clinical relevance because of the increasing action on detrusor muscle and a sensitizing activity on blad-evidence that COX inhibitors produce pain relief during renal der afferents which set the gain for the activation of the colic (Holmlund & Sjodin, 1978;Lundstrom et al, 1982;Oosterlink et al, 1990). …”
Section: Introductionmentioning
confidence: 99%
“…The use of synthetic prostaglandin inhibitors, such as nonsteroidal anti-inflammatory drugs (NSAIDs), is considered nowadays the best and most effective way of treating patients who suffer from renal colics [4,6,7]. Nevertheless, NSAIDs exert undesirable side effects on the excretory tract: Perlmutter et al [8] demonstrated that the use of NSAIDs in subjects with acute obstruction of the excretory tract greatly reduces PRF, which remains low for a long period of time.…”
Section: Introductionmentioning
confidence: 99%